Análisis de los Préstamos Otorgados por la Caja de Ahorro y Crédito “El Manizal”, Período 2014 – 2015 - Ponce Ponce, José Antonio (2017)
The analysis of the loan portfolio is of great importance within financial institutions, however, the same approaches and tools must be used to analyze in a non-profit entity, as in any other entity, in order to make a diagnosis of the situation, whose results support decision-making. The present research was developed under descriptive research methodology at an applied level, where the scientific, inductive, deductive, and statistical method was used, as well as techniques such as bibliographic review, survey, interview and direct observation that complemented the work of countryside. For this reason, the general objective of this thesis is: "To analyze the loans granted by the Savings and Credit Savings Bank El Manizal - Paltas canton - province of Loja, during the period 2014 - 2015", and to comply with it, It was necessary to develop specific objectives such as: Analyze the credit portfolio during the period 2014 - 2015 to determine its structure and progress in the two years, taking into account that the entity has a total of $ 209919.26 in assets, of which the portfolio Represents 67%, which is made up of microcredit, housing, consumer credit and emerging credit. In addition, the horizontal analysis shows that the loan portfolio grew by 6.04% and the delinquency also increased to 15%; Within the second objective, the process of granting the loan is diagnosed, in order to determine the current conditions of the loan, where it is defined that the problem of delinquency depends on the entity and not on secondary problems regarding the payment capacity of the partners. In compliance with the third objective, an improvement plan is designed to strengthen the quality of loan granting and recovery in the "El Manizal" Savings and Credit Fund. The fourth objective complies with the socialization of the thesis work with the managers of the whole entity, who made their contribution and approval of the improvement proposals.